The Quest for Carbenic Nitrile Imines: Experimental and Computational Characterization of C‐Amino Nitrile Imine. Issue 34 (22nd October 2015) - Nunes, Cláudio M.; Reva, Igor; Rosado, Mário T. S.; Fausto, Rui
Abstract: C ‐Amino nitrile imine has been generated as primary photoproduct ( λ = 220 nm) of 5‐amino‐2 H ‐tetrazole isolated in an argon matrix at 15 K. Subsequent photochemical experiments ( λ = 330 nm) demonstrated that C ‐amino nitrile imine isomerizes to the corresponding three‐membered‐ring 1 H ‐diazirine and decomposes to methylenimine. The experimentally observed νas (CNN) absorption at 1998 cm –1 and a carbenic resonance structure contribution of around 20 %, predicted by natural resonance theory calculations, demonstrate that the protoproduced C ‐amino nitrile imine has significant carbenic character. These results pave the way to the discovery of carbenic nitrile imines. Abstract : C ‐Amino nitrile imine has been generated in a low‐temperature matrix. Experimental and computational characterization has demonstrated that C ‐amino nitrile imine has significant carbenic character. These results pave the way to the discovery of carbenic nitrile imines.